Warming Up the Language Engines: Short-Term Second Language Use Increases Subsequent Fluency - Shintel, Hadas; Faust, Miriam (Frontiers in Communication, 2018)
Subjective experience suggests that using one’s second language (L2) becomes easier after an initial period of adjustment. We report the results of an experiment suggesting that even a brief period of L2 use can facilitate subsequent retrieval. Native Hebrew speakers completed letter and category verbal fluency tasks in English. In a subsequent experimental session, participants performed a short comprehension or production task, either in Hebrew (L1) or in English (L2), and then completed an additional round of the English fluency tasks. English use resulted in a reliable improvement in letter fluency, associated with executive functioning. However, there was no reliable improvement in category fluency, associated with lexical knowledge. No reliable improvement in the fluency tasks was observed following Hebrew use. Results suggest that even a brief period of L2 use can facilitate retrieval, by increasing the relative activation of L2. Furthermore, improvement did not result from priming specific lexical items, suggesting increased relative activation affects the L2 lexicon as a whole.